Understanding sex differences in depressive symptomatology among Malaysian adolescents - Barra, Sharisse May Mate; Baharudin, Rozumah; Zulkefly, Nor Sheereen; Yahya, Amira Najiha; Madon, Zainal (KITE E-Learning Solutions, 2019)
Depressive symptomatology is among the primary psychological problems experienced by adolescents. Extant literature has also extensively reported sex diferences in the occurrence of depressive symptoms. However, a majority of related research has primarily been carried out in the Western context. Hence, we conducted a study to identify the prevalence of depressive symptoms among Malaysian adolescents, and to determine its relationship with certain risk factors as well as the potential moderating role of sex. The sample comprised of 964 adolescents from 20 secondary schools across Malaysia. Logistic regression results demonstrated that stressful life events and maternal verbal aggression signifcantly predicted symptoms of depression. In moderation tests, sex signifcantly interacted with stressful life events and parental verbal aggression in predicting depressive symptoms. Hence, there is evidence to suggest that the depressogenic impact of stressful life events and parental verbal aggression on depressive symptomatology difers between male and female adolescents.